Microstructure and properties of WC–Co cemented carbide/40Cr steel joints brazed at low–temperature with Ag–Cu–In–Ti filler alloy. (February 2023) - Zheng, Zhaoyang; Shao, Shuai; Xu, Minyun; Ma, Ruina; Du, An; Fan, Yongzhe; Zhao, Xue; Cao, Xiaoming
Abstract: WC–Co cemented carbide/steel brazed at low–temperature is of significant scientific and technical interest. In this study, the interface microstructure between the filler alloy and WC–Co and 40Cr steel, the formation process of the joint microstructure, and the effect of brazing temperature on the microstructure and properties of joints were systematically studied. The filler alloy was bonded by forming a TiC reaction layer with WC–Co and 40Cr steel, which enhanced the retention of the filler layer on the joint. The microstructure of the joint was a WC–Co/TiC reaction layer/TiCo reaction layer/Cu2 InTi + eutectic structure (Ag [s, s] + Ag–doped Cu7 In3 + Cu4 In) + Cu [s, s]/TiC reaction layer/40Cr steel. Moreover, the maximum average shear strength of the joint (brazed at 740 °C) reached 258 MPa, which is approximately 60% higher than those reported in the literature. The fracture behavior of the joint was mainly affected by the distribution of the Cu2 InTi intermetallic compounds in the filler layer and the diffusion of Co from the cemented carbide. Highlights: WC–Co cemented carbide and 40Cr steel was brazed at low–temperature (700–780 °C) with Ag–Cu–In–Ti filler alloy. TiC reaction layer was formed at the interfaces of WC–Co/filler alloy and 40Cr steel/filler alloy after brazed, ensuring the perfect combination of the interface. The maximum average shear strength of the joints (brazed at 740 °C) can reach 258 MPa, which is enhanced approximately 60%. The joint dependence of fracture behaviors on joint microstructures was clarified.